A Phase II Study of Concurrent Docetaxel, Epirubicin and Cyclophosphamide as a Neoadjuvant Chemotherapy Regimen in Patients with Locally Advanced Breast Cancer - Yao, Xin (Ivyspring International Publisher, 2012)
Background: Neoadjuvant chemotherapy with concurrent docetaxel, doxorubicin and cyclophosphamide is commonly used for patients with locally advanced breast cancer. Epirubicin is another anthracycline used in breast cancer but the concurrent use of epirubicin and taxane is not well-established. We conducted a single institution, phase II study to assess the efficacy and safety of concurrent docetaxel, epirubicin and cyclophosphamide (TEC) as a neoadjuvant chemotherapy regimen in breast cancer. Methods: Patients with newly diagnosed locally advanced breast cancer defined as T2 >3 cm, T3, T4 with any N, or any T with N1-3 were eligible. A chemotherapy regimen of docetaxel 75mg/m(2), epirubicin 75mg/m(2) and cyclophosphamide 600mg/m(2 )was given with filgrastim support every 3 weeks for 6 cycles. The primary end-point was pathologic complete response rate. Results: Twenty patients were enrolled from 2003 to 2006. The median age was 51 (29-70) year-old. Eight patients were premenopausal. Ten patients had positive hormone receptors. Four patients had HER2 positive receptor. Nineteen patients completed six cycles of TEC chemotherapy. The pathologic complete response rate was 25%. Eight of sixteen patients with N1-3 disease had pathological negative lymph nodes. With a median follow up of 57.5 (16-71) months, four patients relapsed including one death from recurrence. The estimated 5 year relapse-free survival was 79.3% and the 5-year overall survival was 94.7%. No patient had cardiac failure or death during treatment. The most common grade 3-4 toxicity was neutropenia (35%). Conclusion: TEC regimen is a well- tolerated and effective neoadjuvant chemotherapy regimen for locally advanced breast cancer that results in a pathologic complete response rate of 25%.